Evaluation of Medication Use Pattern Among Patients Presenting to the Emergency Department of Hiwot Fana Specialized University Hospital, Using WHO Prescribing Indicators - Mishore, Kirubel Minsamo; Girma, Yabsira; Tola, Assefa; Mekuria, Abraham Nigussie; Ayele, Yohanes (Frontiers in Pharmacology, 2020)
Abstract Background: Ensuring rational drug use need ongoing evaluation of drug prescribing, dispensing and use by patients. Health care providers working in emergency department face unique challenges including making urgent decisions, patient overload and limited resource contributing for inappropriate drug use. The rational medication use should be the important aspect of emergency care to improve patient outcomes. Thus, this study was conducted to assess medication utilization pattern using World Health Organization (WHO) prescribing indicators in the emergency department Methods: A cross sectional study design was implemented among patients presented to the emergency department of at Hiwot Fana Specialized University Hospital (HFSUH) from January to March 2018. The data were collected from a total of 342 patients’ medical charts using pre-prepared structured format according to WHO recommendation. The data were analyzed using SPSS version 21 software and presented in tables and figures. Results: The commonly reported clinical diagnosis was found to be soft tissue laceration or abrasion 75 (21.9%) followed by dyspepsia 50(14.6%) and severe pneumonia 44 (12.9%). A total of 810 drugs were prescribed for 342 patients. The main category of drugs prescribed were analgesic constituting 125(29.2%) followed by antibiotics 120 (28.0%). Regarding to WHO prescribing indicators, the average number of drugs prescribed per encounter was 2.36, percentage of encounters with antibiotics was 127(37.13%) and injections were prescribed for 300 (87.7%) of encounters. All of the drugs prescribed were from the National Essential Medicine List (NEML) for Ethiopia and 780 (98.1%) of drugs were prescribed by international nonproprietary name. Conclusion: Overall, there were inflated use of antibiotics and injection drugs whereas prescribing by international nonproprietary name and prescribing from NEML were according to the recommendation. Hence, the hospital should work to ensure judicious use of antibiotics and injection drugs.